Trimmed off adipocytes: a source of newly secreted adiponectin - Azahari, Nuraniza; Khattak, Muhammad Muzaffar Ali Khan; Mohd-Shukri, Nor Azwani; Abdul Rahman, Suzanah; Osman Idid, Syed Zahir Idid Syed; Chia, Phang Ing; Md Isa, Muhammad Lokman; Md. Aris, Mohd Aznan; Taher, Muhammad (Progress in Nutrition, 2019)
Given the beneficial roles of adiponectin on body metabolism and its profound protective effects against metabolic disease, a better understanding of the adiponectin secretion is very important.  The objective of this study was to isolate, detect and quantify total adiponectin in trimmed off abdominal adipose tissues from halal meat sources namely chicken, beef and lamb. Abdominal adipose tissues were isolated from the aforementioned sources and delipidation of the tissues were performed by chloroform/methanol extractions. Afterwards, the protein concentration was determined by using Protein Assay Bicinchoninate Kit method. This was followed by quantification of the adiponectin using ELISA kit assay. The experiment was conducted in triplicates and the results are presented as means ± SD. The data was statistically analyzed using SPSS (Version 21.0). One-way analysis of variance (ANOVA) was used and the means were considered statistically different at 95% confidence interval. Results indicate that the extraction of 10 gram subcutaneous adipose tissues from chicken, beef and lamb yielded 0.10 gram, 0.15 gram and 0.15 gram respectively of protein amount which was 1 to 1.5 % from total tissue mass. The protein concentration in abdominal adipose tissue from chicken, beef and lamb were 1.25 ± 0.05, 1.75 ± 0.05 & 2.53 ± 0.07 mg/ml, respectively. The isolated adiponectin concentration in chicken, beef and lamb were 158 ng/ml± 0.05, 24 ± 0.05µg/ml and 37 ± 0.08 ng/ml, respectively. Adiponectin concentration in beef abdominal adipose tissue was significantly (p